FORMULASI DAN UJI MUTU FISIK MASKER PEEL OFF PATI KENTANG (Amylum solani) SEBAGAI EKSFOLIASI KULIT WAJAH - Rusmin, Rusmin; hafid, muliana; Nurinayah, Nurinayah (Journal Pharmacy and Application of Computer Sciences, 2023)
The aim of the study was to formulate peel off masks and test the physical quality of potato starch peel off masks (Amylum solani) as facial skin exfoliants. This research was carried out in the Phytochemical and Pharmaceutical Laboratory of Pancasakti University-Makassar. The process of making starch begins with mashed potatoes and let stand for 24 hours with distilled water to get starch filtrate. The starch obtained is then dried and sieved. Potato starch is formulated into face mask preparations and physical quality tests are carried out in the form of organoleptic tests, homogeneity tests, pH tests, viscosity tests, spreadability tests, drying time tests and hedonic tests. The results of the physical quality test of the preparations showed that there was an effect of variations in the concentration of potato starch on the stability of facial skin cleansing mask preparations. However, the results of the physical quality of the preparation still meet the stability requirements for facial skin cleansing mask preparations. Thus the use of variations in the concentration of potato starch can be formulated for exfoliating facial skin masks.